Hubungan Pengetahuan dan Motivasi Ibu dalam Upaya Stimulasi Pertumbuhan dan Perkembangan Bayi - Maulidia, Khasanah (Agribiohealth (Journal of Agriculture, Biology & Health Sciences), 2025)
Child development is a continuous process that begins at birth and continues throughout life, with infancy representing a critical period that determines future physical, mental, and social abilities. To achieve optimal growth and development, infants require not only adequate nutrition and affection but also appropriate and consistent stimulation. Mothers play a crucial role in providing early stimulation, as sufficient knowledge enhances motivation to engage in activities that support infant development. This study aimed to analyze the relationship between the level of maternal knowledge and mothers’ motivation in providing stimulation for infant growth and development. An analytic survey with a cross-sectional design was conducted among 91 mothers with infants in Sukani PMB, selected through simple random sampling. Data were collected using a structured questionnaire and analyzed using the Chi-square test at a 0.05 significance level. The results showed a significant association between maternal knowledge and motivation to provide stimulation (p < 0.001), with a strong correlation between the two variables. These findings suggest that higher maternal knowledge is associated with greater motivation to support infant development. Strengthening health education and counseling programs for mothers is recommended to enhance family participation in promoting optimal child growth and development.